Extending immigration policing and exclusion in the UK. (January 2014) - Webber, Frances
This piece contains the responses to two consultations by the UK government on proposals to place duties on private landlords to act as extensions of the immigration service in order to exclude undocumented migrants from rented accommodation, and to exclude all migrants, except permanent residents, from free National Health Service (NHS) healthcare. The author comments on the likely effects and the larger human rights implications.